Preparation of secondary school teachers in the College of Education of the University of the Philippines and its implications in the Dhanamanjari College, Manipur - Devi, Nonthombam (Mema) 1943- (s.n.], 1969)
The main purpose of the study is to to investigate the practices, mainly of the recruitment and selection of trainees, curriculum-general education, professional education and subject specialization, student-teaching and co-curricular activities, of the education of secondary school teachers in the College of Education of the University of the Philippines and to determine the implications for the enrichment of the pre-service education programme of secondary school teachers in the Dhanamanjari College, Manipur.